2006
DOI: 10.1159/000096222
|View full text |Cite
|
Sign up to set email alerts
|

Postnatal Development of the Primate Hippocampal Formation

Abstract: The hippocampal formation is a multicomponent region of the medial temporal lobe preferentially involved in declarative and relational memory processing. Behavioral studies have suggested a protracted functional maturation of these structures in primates, and postnatal developmental abnormalities in the hippocampal formation are thought to contribute to neurodevelopmental disorders, such as autism, schizophrenia, epilepsy and Down syndrome. Despite all that we know about the functional organization of the adul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
72
4

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 83 publications
(82 citation statements)
references
References 128 publications
6
72
4
Order By: Relevance
“…This would result in gradually increasing pre-awakening inhibition of cortisol secretion and decreasing cortisol levels on awakening with infant development. Although being speculative, this interpretation is also in line with evidence showing that particularly the hippocampus is a structure undergoing major changes during the first nine months of life (see Arnold and Trojanowski, 1996;Lavenex et al, 2007).…”
Section: Discussionsupporting
confidence: 79%
“…This would result in gradually increasing pre-awakening inhibition of cortisol secretion and decreasing cortisol levels on awakening with infant development. Although being speculative, this interpretation is also in line with evidence showing that particularly the hippocampus is a structure undergoing major changes during the first nine months of life (see Arnold and Trojanowski, 1996;Lavenex et al, 2007).…”
Section: Discussionsupporting
confidence: 79%
“…The fact that the hippocampus receives via the TS direct input from all of the primary and multi-modal sensory cortices of the brain (Lavenex et al 2007), suggests that any damage to the TS has the potential to disrupt input-output integrity of hippocampal function and MTL integration of the medial temporal lobe with the rest of the brain. Indeed, Gaffan (2005) argues that 'memory' impairment is not so much dependent upon damage specific to the hippocampus as it is to the disruption of pathways that interconnect the hippocampus to the rest of the brain (see also Diehl et al 2008;Taoka et al 2008;Wang et al 2008).…”
Section: Memory Neurobehavioral Sequelaementioning
confidence: 99%
“…However, developmental changes in baseline PV expression within typically developing behaviorally and pharmacologically naïve rats have not yet been systematically studied across the life span. Importantly, characterization of PV with respect to distinct HPC subregions and across the septotemporal extent, as well as in neocortical regions throughout development, is lacking [50]. In pilot studies, we have observed a roughly 10-20% decrease in PV cell counts in 6-month- compared to 1-month-old rats, with significant regional and septotemporal variation [51].…”
Section: Introductionmentioning
confidence: 99%